Idiopathic Basal Ganglia Calcification Presented with Impulse Control Disorder. (13th July 2015) - Sahin, Cem; Levent, Mustafa; Akbaba, Gulhan; Kara, Bilge; Yeniceri, Emine Nese; Inanc, Betul Battaloglu
Abstract : Primary familial brain calcification (PFBC), also referred to as Idiopathic Basal Ganglia Calcification (IBGC) or "Fahr's disease, " is a clinical condition characterized by symmetric and bilateral calcification of globus pallidus and also basal ganglions, cerebellar nuclei, and other deep cortical structures. It could be accompanied by parathyroid disorder and other metabolic disturbances. The clinical features are dysfunction of the calcified anatomic localization. IBGC most commonly presents with mental damage, convulsion, parkinson-like clinical picture, and neuropsychiatric behavior disorders; however, presentation with impulse control disorder is not a frequent presentation. In the current report, a 43-year-old male patient who has been admitted to psychiatry policlinic with the complaints of aggressive behavior episodes and who has been diagnosed with impulse control disorder and IBGC was evaluated in the light of the literature.